A The ACCOUNTING FOR THE TEMPERATURE DISTRIBUTION OF A BODY IN THE FORM OF A RECTANGULAR PARALLELEPIPED, TAKING INTO ACCOUNT HEAT TRANSFER USING A VARIATIONAL APPROACH: ACCOUNTING FOR THE TEMPERATURE DISTRIBUTION OF A BODY IN THE FORM OF A RECTANGULAR PARALLELEPIPED, TAKING INTO ACCOUNT HEAT TRANSFER USING A VARIATIONAL APPROACH (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Finite element method is a numerical method solutions of differential equations, found in physics and technology. The emergence of this method associated with solving problems of space research. It was first published in the work of Turner, Cluj, Martin and Topp. This work contributed to the emergence of other works; a number of articles have been published with examples of the finite element method to the problems of construction mechanics of continuous media. The main idea behind the finite element method is that any continuous quantity such,like temperature pressure and displacement, can be approximated by a discrete model, which is built into a set of piece-continuous functions defined on a finite number of subdomains.The main idea of the finite element method is that any continuous quantity, such as temperature, pressure and displacement, can be approximated by a discrete model, which is built on a set of piece-continuous functions definedon a finite number of subdomains.
Keywords: Finite element, pipe, motion, cross section, compression, lubrication, system, vibration, equilibrium, continuous value, discrete model, node.